Concept of Financial Management in Islamic Perspective - Marsuni, Nur Sandi; Yusuf, Muhammad; K, M. Yusuf (Invoice : Jurnal Ilmu Akuntansi, 2022)
Financial management, also known as financing management, is a money arrangement that involves the source, allocation, usage, and responsibility of funds utilized to meet the organization's or institution's goals. Financial performance will be more efficient if the organization/institution has good financial management. The goal of this research was to look at the notion of financial management from an Islamic standpoint. This is a form of research that takes place at a library. The researchers in this study took a literature review and analytical technique. The researcher uses the descriptive analytical approach to acquire data that has been analyzed. Meanwhile, to achieve adequate study outcomes, the validity of the examination employs analytical persistence procedures. The findings show that the verses of the Koran that are relevant to the concept of financial management are found in the letter Al-Furqon verse 67, which discusses everything related to financial management, including being frugal, not luxurious, efficient, and appropriate, as well as being open and transparent. Surah As-Al-Hasyr verse 18 talks about paying attention to what has already been done in order to plan for the future. Because all laws essentially return to the Al-Quran and As-Sunnah, Al-Quran verses that are important to financial management are utilized as a reference in their implementation and can overcome challenges in the financial administration of companies or institutions